Sponsored links: Algebra eBooks
 

Related

nusum-ratexpand

f(x,a,y,b,d,p) := p[0...

h(x,a,y,b,d,p) := rat...

h(x,a,y,b,d,p);

Calculate

nusum

f(x,a,y,b,d,p) := p[0...

g(y) := nusum(f(k,a,y...

g(y);

Calculate

nusum

nusum(k*(3*k-2),k,1,n);

Calculate

nusum

nusum(k*(k+1)*2^k,k,1...

Calculate

nusum

nusum(i*a**i,i,0,m-1)...

Calculate

nusum

nusum(k*(k+1)*2^k,k,1...

Calculate

nusum

nusum(1/k!*x^k,k,0,5);

Calculate

nusum

nusum((2*k-1)*(k-3),k...

Calculate

nusum-ratexpand

f0(x,a,y,b,d,p) := p[0];

f1(x,a,y,b,d,p) := p[...

f2(x,a,y,b,d,p) := p[...

Calculate

nusum

f(x,a,y,b,d,p) := nus...

g(y) := nusum(f(k,a,y...

g(y);

Calculate

nusum

Run Example
(%i1)ratsimp(x*(4*x^2+9*x-1)/6-x*(x+1)*(2*x+1)/3-x*(x+1)/2);
(%o1)                                 - x
(%i2) nusum((2*k-1)*(k+1),k,1,n);
                                    2
                              n (4 n  + 9 n - 1)
(%o2)                         ------------------
                                      6
(%i3) sum(2*k^2+k-1,k,1,n);
                              n
                             ====
                             \         2
(%o3)                         >    (2 k  + k - 1)
                             /
                             ====
                             k = 1
(%i4) 
Run Example
sum(((A^n-A^k)/(A^n-1))/A^k,k,0,n-1);
                                 n - 1
                                 ====   n    k
                                 \     A  - A
                                  >    -------
                                 /        k
                                 ====    A
                                 k = 0
(%o1)                            -------------
                                     n
                                    A  - 1
(%i2) simplify(%);
(%o2)        simplify(nusum(A^(n-k)-1,k,0,n-1);
Run Example
sum (n^4*4^n/binomial(2*n,n), n, 0, inf);
                            inf
                            ====        4  n
                            \          n  4
(%o1)                        >    ----------------
                            /     binomial(2 n, n)
                            ====
                            n = 0
(%i2)  unsum (%, n);
(%o2)                                  0
(%i3)  unsum (prod (i^2, i, 1, n), n);
                           n - 1
                           /===\
                            ! !   2
(%o3)                     ( ! !  i ) (n - 1) (n + 1)
                            ! !
                           i = 1
(%i4)  nusum (%, n, 1, n);
(%o4)            

Related Help

Help for Nusum